2008
DOI: 10.1590/s1516-14392008000400017
|View full text |Cite
|
Sign up to set email alerts
|

Chemsensor of NO2 gas based on porphyrin of 5, 10, 15, 20-tetraphenylporphyrin LB films and LS films

Abstract: The sensitivity of 5, 10, 15, 20-tetraphenylporphyrin (H 2 TPP) to the presence of NO 2 gas in diluted solutions and in Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) films was investigated by UV-visible spectroscopy. The shift of Soret and Q bands were analyzed and the energies involved were calculated. The exposure of LB porphyrin films deposited onto glass slides to NO 2 has performed as an active chemsensor with 7000 ppm gas concentration. Furthermore, the UV-vis dichroism absorption results associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Free‐base and metallated porphyrin films were thoroughly investigated in order to use them in sensing of, for instance, gaseous ammonia 15, NO 2 17, 18, oxygen 19, 20, different volatile organic compounds (ethanol, acetic acid, dimethylsulfide, triethylamine, 4‐aminophenol, pyridine, acetonitrile, acetone, tetrahydrofuran, chloroform, dichloromethane, benzene and so forth) 3, 21, 22, compounds in liquid phases such as different L‐amino acids 23 and medium, pH 6, 24. Apparently, tiny wave‐guiding channels of PCF can also be modified by photo‐ and environmental sensitive SAMs, and therefore can be used in sensor applications using the same detection principles as those for TOFs.…”
Section: Resultsmentioning
confidence: 99%
“…Free‐base and metallated porphyrin films were thoroughly investigated in order to use them in sensing of, for instance, gaseous ammonia 15, NO 2 17, 18, oxygen 19, 20, different volatile organic compounds (ethanol, acetic acid, dimethylsulfide, triethylamine, 4‐aminophenol, pyridine, acetonitrile, acetone, tetrahydrofuran, chloroform, dichloromethane, benzene and so forth) 3, 21, 22, compounds in liquid phases such as different L‐amino acids 23 and medium, pH 6, 24. Apparently, tiny wave‐guiding channels of PCF can also be modified by photo‐ and environmental sensitive SAMs, and therefore can be used in sensor applications using the same detection principles as those for TOFs.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Briefly, the easiest way to get the orientation of the porphyrin rings is to measure the dichroic ratios • (D 45 ). Then, it was calculated the orientation angles normal to the film (θ ) and the dipping direction (ϕ) by the following equations:…”
Section: Molecular Orientation Of Porphyrin Filmsmentioning
confidence: 99%
“…[1,18,21] The orientation angles were calculated using Eqns (1) and (2). Considering the uncertainty of ±5…”
Section: Molecular Orientation Of Porphyrin In Lb and Ls Filmsmentioning
confidence: 99%
“…While phthalocyanines have been most commonly employed as chemical sensors [3] [4], less work has been devoted to use porphyrin and metalporphyrin films in spite that this molecule plays a key role as active organic material for various biological processes [5]. Over the last few years, some experiments have been carried out to investigate the sensitivity of porphyrins in solution [6], thin films formed with the Langmuir-Blodgett technique [7] [8] [9] [10] and spin-coating [11] to detect volatile compounds. On the other hand, Roales et al [12] showed the influence of the porphyrin central metal group in the sensing response of volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the zinc porphyrin film exhibited by far the most important changes among different central metal atoms. Furthermore, metal and metal free porphyrin films have been employed to detect CO 2 and NO 2 toxic gases, among others [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%